Approximations of steady periodic water waves in flows with constant vorticity. (October 2015) - Constantin, A.; Kalimeris, K.; Scherzer, O.
Abstract: We provide high-order approximations to periodic travelling wave profiles and to the velocity field and the pressure beneath the waves, in flows with constant vorticity over a flat bed.